OPTIMASI JUMLAH CLUSTER METODE K-MEDOIDS BERDASARKAN NILAI DBI PADA PENGELOMPOKKAN DATA LUAS TANAMAN DAN PRODUKSI KELAPA SAWIT DI SUMATERA UTARA - Darmeli Nasution; Donna N.M. Sirait; Ivana Wardani; Dwiyanto Dwiyanto (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2022)
North Sumatra is the center of oil palm plantations in Indonesia. Palm oil is one of the leading commodities in North Sumatra province. Based on BPPS, North Sumatra has a very large land area of 440,000 ha and production yields of 7,000,000 tons. This study focuses on grouping the area of plantations and oil palm production in the districts/cities of North Sumatra province using the K-Medoids clustering method. In this grouping, several forms of the number of clusters are used to obtain a more optimal grouping. Each form of the number of clusters in this grouping is evaluated based on the DBI value. The smallest DBI value is the best form of the number of clusters in grouping plant area and oil palm production using K-Medoids. The results of this study indicate that the form of the number of clusters 2 is the best form of the number of clusters with a DBI value of 0.099.Keywords: Data mining, Clustering, K-Medoids, Davies Bouldin Index.Sumatera Utara merupakan sentral perkebunan sawit di Indonesia. Kelapa sawit merupakan salah satu komoditas unggulan propinsi Sumatera Utara. Berdasarkan BPPS Sumatera Utara memiliki lahan yang sangat luas mencapai 440.000 ha dan hasil produksi mencapi 7.000.000 ton. Penelitian ini memfokuskan pada pengelompokkan luas tanaman dan produksi kelapa sawit di kabupaten/kota propinsi Sumatera Utara menggunakan metode K-Medoids clustering. Pada pengelompokkan ini menggunakan beberapa bentuk jumlah cluster untuk mendapatkan pengelompokkan yang lebih optimal. Masing-masing bentuk jumlah cluster pada pengelompokkan ini di evaluasi berdasarkan nilai DBI. Nilai DBI terkecil merupakan bentuk jumlah cluster terbaik pada pengelompokkkan luas tanaman dan produksi kepala sawit menggunakan K-Medoids. Hasil penelitian ini menunjukkan bentuk  jumlah cluster 2 merupakan bentuk jumlah cluster terbaik dengan nilai DBI 0,099.Kata kunci: Data mining,  Clustering, K-Medoids, Davies Bouldin Index.